European traffic on road bridges and recalibration of damage equivalence factor for fatigue verification. Issue 2 (1st September 2021) - Bianchi, Gianluca; Nussbaumer, Alain; Pedro, José J. Oliveira
Abstract: The evolution of European traffic, combined with the current revision works of the Eurocodes (CEN250 project 2 nd Eurocode generation), represents an opportunity to improve the simplified method for fatigue checks (also known as the lambda method) for road bridges. The works reported herein focus on the reassessment of the λ1 factor curves for the damage effect of highway traffic on road bridges, using the existing Eurocode FLM3 model. The aim of the research is to model the traffic and resulting stress ranges at details on bridges with different static systems. The simulation results shall be as similar as possible to reality by introducing different parameters that were not taken into account in the EN 1993‐2 background simulations [1, 2], including the passage of multiple vehicles at the same time in the flowing and congested traffic conditions. The development of new λ1 factor curves lead to a different classification into midspan bending moment, shear force, and support midspan and shear force. Within this study, the validity of the formulas for λ2 and λ3 were also checked. The new curves have less dispersion and may be taken into consideration to update the current curves from EN 1993‐2.